Teleworking During Pandemic Covid-19 in Indonesia, and The Impact of Flexible Working Hours - Retno Fuji Oktaviani; Rinny Meidiyustiani; Hakam Ali Niazi; Syaiful Anwar (International Journal of Business Studies, 2022)
This study aims to determine factors and analyze company's readiness to adopt teleworking proper to the Covid-19 situation. Working is significant during a pandemic so that companies can keep running, fulfill employee rights and have an impact on other benefits such as being able to reorganize economic conditions, traffic and the situation in congested cities. Therefore, it’s significant to recognize what helps a company's work transition to be successful. A pandemic situation is a natural challenge that enables individuals and organizations to increase their aptitude to adjust to unpredictable environmental changes quickly. This research is based on a observe establish in December 2020 through the lockdown period in several regions in Indonesia so that data collection is carried out online. Final sample consisted of 95 observations. Using path analysis, by modeling the conditions of the Covid-19 pandemic as a mediator of organization, technology and human resources in influencing teleworking adoption. Teleworking is also modeled with the resulting effect, namely flexible working hours. The results show that the Covid-19 pandemic situation can moderate the influence of organizations and human resources on teleworking adoption and also that teleworking adoption affects flexible working hours. by modeling the conditions of the Covid-19 pandemic as a mediator of organization, technology and human resources in influencing teleworking adoption. Teleworking is also modeled with the resulting effect, namely flexible working hours. The pandemic situation may moderate the influence of organizations and human resources on teleworking adoption and also that teleworking adoption affects flexible working hours.